Metabolomics and Transcriptomics Analysis of Pollen Germination Response to Low-Temperature in Pitaya (Hylocereus polyrhizus) - Dai, Hong-fen; Jiang, Biao; Zhao, Jun-sheng; Li, Jun-cheng; Sun, Qing-ming (Frontiers in Plant Science, 2022)
Cross-pollination can improve the percentage of fruit set and fruit weight for most of red flesh varieties in pitaya. The technology of pollen storage was very important for successful cross-pollination. However, till now, technology of pollen storage is not satisfactory in pitaya production. In this study, pitaya pollen stored at low temperature was taken as the research object, physicochemical indexes, metabolomics and transcriptomics of which were studied. The results showed that in vitro pollen germination rate decreased significantly with the increase of storage time. Soluble sugar and soluble protein content of pollen reached the peak value on the first day of storage, relative conductivity, manlondialdehyde (MDA) and proline content of which increased gradually during storage. At the same time, the antioxidant enzyme system of pollen was also affected. Superoxide dismutase (SOD) activity decreased, while the activities of catalase (CAT) and peroxidase (POD) increased and superoxide anion generation rate increased gradually during storage. According to the metabolomics results, amino acids, peptides, nucleotides, plant hormones, terpenes, alcohols, phenols, flavonoids, sterols, vitamins, esters, sphingolipids and ketones content increased significantly during storage, flavonoids and pigments content declined gradually. During pollen storage, the gene expressions related to carbohydrate metabolism, protein metabolism, acid and lipid metabolism, sterol metabolism, plant hormone metabolism and signal transductions were significantly down-regulated. With KEGG pathway analysis, Isoquinoline alkaloid biosynthesis, Tyrosine metabolism, Alanine, aspartate and glutamate metabolism of pollen were affected significantly during low temperature storage. Correlation analysis showed that the gene expression patterns of HuRP2, HuUPL1 and HuAAT2 had significant effects on the pollen germination. D-arabinose 5-phosphate and myricetin were positively correlated with pollen germination rate, which were valuable or researching preservation agents. In this study, the changes of pollen during low temperature storage were described from the level of metabolites and genes, which could provide theoretical support for the research and development of pollen long-term storage technology in pitaya. Keywords: pitaya, in vitro pollen germination, low temperature storage, transcriptomics, metabolomics